2021
DOI: 10.47836/pjssh.29.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Salience in the Media and Political Trust in Nigeria: The Mediating Role of Political Participation

Abstract: Political distrust is prevalent in many parts of the world. Scholars have discovered many factors affecting political trust, but they have paid little attention to the influence of issue salience in the media on political trust. Focusing on the role of media in assigning salience to corruption issues in Nigeria, this study examined the influence of mainstream media and social media on political trust. In addition, we treated political participation as a mediating factor and investigated its effect on the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
0
0
1
Order By: Relevance
“…Corruption, involving bribery, money laundering, misappropriation of funds, along with the accumulation of wealth by Nigerian leaders have also been found to exacerbate this trust deficit. This finding is consistent with Akinola et al (2021), who also emphasized the influence of religious membership, political participation, and corruption management on political trust in Nigeria.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Corruption, involving bribery, money laundering, misappropriation of funds, along with the accumulation of wealth by Nigerian leaders have also been found to exacerbate this trust deficit. This finding is consistent with Akinola et al (2021), who also emphasized the influence of religious membership, political participation, and corruption management on political trust in Nigeria.…”
Section: Resultssupporting
confidence: 90%
“…The study found that there are different predictors for trust in each level of government. Akinola et al (2021) conducted a review study that employed a microlevel analysis of public opinion survey data (question by question) to explore the empirical linkages of political trust within Nigeria. The study utilised data from the Afrobarometer Survey Round 4 carried out in 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dengan situasi pandemik COVID-19 pada masa kini, kawalan pergerakan warga asing adalah sangat kritikal. Malah, pengurusan Program MM2H adalah bertepatan dengan skop kerja di bawah JIM di mana urusan pengeluaran visa dan pas adalah lebih sistematik dan boleh dipercepatkan jika Program MM2H diletakkan di bawah bidang kuasa JIM.Kenyataan ini dapat dikukuhkan lagi dengan kajian olehAkinola et al (2021) yang telah dijalankan di Nigeria. Dapatan kajian tersebut memaparkan bahawa penggunaan platform media sosial (kerajaan dan rakyat) mampu meningkatkan kepercayaan dan sokongan rakyat terhadap kerajaan.Selain itu, hebahan dan perkongsian aktiviti daripada Pusat MM2H seperti menyenaraikan aktiviti-aktiviti yang melibatkan peserta MM2H (Contohnya: Majlis Hitea, Program bahasa kebangsaan, kerja amal, dan sebagainya) dilihat mampu menarik minat pelancong atau pelabur asing untuk menyertai MM2H.…”
unclassified